The Objective Physical Activity and Cardiovascular Disease Health in Older Women (OPACH) Study. (December 2017) - LaCroix, Andrea; Rillamas-Sun, Eileen; Buchner, David; Evenson, Kelly; Di, Chongzhi; Lee, I-Min; Marshall, Steve; LaMonte, Michael; Hunt, Julie; Tinker, Lesley; Stefanick, Marcia; Lewis, Cora; et al.
Abstract Background Limited evidence exists to inform physical activity (PA) and sedentary behavior guidelines for older people, especially women. Rigorous evidence on the amounts, intensities, and movement patterns associated with better health in later life is needed. Methods/Design The Objective PA and Cardiovascular Health (OPACH) Study is an ancillary study to the Women's Health Initiative (WHI) Program that examines associations of accelerometer-assessed PA and sedentary behavior with cardiovascular and fall events. Between 2012 and 2014, 7048 women aged 63–99 were provided with an ActiGraph GT3X+ (Pensacola, Florida) triaxial accelerometer, a sleep log, and an OPACH PA Questionnaire; 6489 have accelerometer data. Most women were in their 70s (40%) or 80s (46%), while approximately 10% were in their 60s and 4% were age 90 years or older. Non-Hispanic Black or Hispanic/Latina women comprise half of the cohort. Follow-up includes 1-year of falls surveillance with monthly calendars and telephone interviews of fallers, and annual follow-up for outcomes with adjudication of incident cardiovascular disease (CVD) events through 2020. Over 63, 600 months of calendar pages were returned by 5, 776 women, who reported 5, 980 falls. Telephone interviews were completed for 1, 492 women to ascertain the circumstances, injuries and medical care associated with falling. The dataset contains extensive information on phenotypes related to healthy aging, including inflammatory and CVD biomarkers, breast and colon cancer, hip and other fractures, diabetes, and physical disability. Discussion This paper describes the study design, methods, and baseline data for a diverse cohort of postmenopausal women who wore accelerometers under free-living conditions as part of the OPACH Study. By using accelerometers to collect more precise and complete data on PA and sedentary behavior in a large cohort of older women, this study will contribute crucial new evidence about how much, how vigorous, and what patterns of PA are necessary to maintain optimal cardiovascular health and to avoid falls in later life. Clinical trials registration ClinicalTrials.gov identifierNCT00000611 . Registered 27 October 1999.